Human capital quality and the immigrant wage gap - Serge Coulombe; Gilles Grenier; Serge Nadeau (IZA Journal of Migration, 2014)
We propose a new methodology for analyzing determinants of the wage gap between immigrants and natives. A Mincerian regression framework is extended to include GDP per capita in an immigrant's country of birth as a proxy for the quality of schooling and work experience acquired in that country. We find that Canadian immigrants' returns to schooling and work experience significantly increase with the GDP per capita of their country of birth. The contribution of quality of schooling and work experience to the immigrant wage gap is also examined. Lower human capital quality completely negates the endowment advantage that immigrants have in the areas of schooling and work experience. Since data on GDP per capita are available for most countries over long periods, the proposed methodology can be applied to analyze immigrant wage gaps for a large set of countries for which common statistics on natives and immigrants are available.
Keywords: J20; J24; J15; J61; 330; Wage differentials; Immigrants vs. Canadian natives; Human capital quality; Immigration policies; Work experience; Education